Twelve tips for integrating team reflexivity into your simulation-based team training. (3rd July 2018) - Schmutz, Jan B.; Kolbe, Michaela; Eppich, Walter J.
Abstract: Due to increasing complexity in healthcare, clinicians must often make decisions under uncertain conditions in which teams must be flexible and process emerging information "on the fly" in order to adapt to changing circumstances. A crucial strategy that helps teams to adapt, learn, and develop is team reflexivity (TR) – a team's ability to collectively reflect on group objectives, strategies, processes, and outcomes of past and current performance and to adapt accordingly. We provide 12 evidence-based tips on incorporating TR into simulation-based team training (SBTT). The first three points elaborate on basic principles of TR, when TR can take place and why it matters. The following nine tips are then organized according to three phases in which teams are able to engage in TR: pre-action, in-action, and post-action. SBTT represents an ideal venue to train various TR behaviors that foster team learning and improve patient care.